Neurocognitive and Quality of Life Improvements Associated With Aerobic Training for Individuals With Persistent Symptoms After Mild Traumatic Brain Injury: Secondary Outcome Analysis of a Pilot Randomized Clinical Trial - Gladstone, Emily; Narad, Megan E.; Hussain, Fadhil; Quatman-Yates, Catherine C.; Hugentobler, Jason; Wade, Shari L.; Gubanich, Paul J.; Kurowski, Brad G. (Frontiers in Neurology, 2019)
OBJECTIVE: To report secondary neurocognitive and quality of life outcomes for a pilot randomized clinical trial (RCT) of aerobic training for management of prolonged symptoms after a mild traumatic brain injury (mTBI) in adolescents. SETTING: Outpatient research setting. PARTICIPANTS: Thirty adolescents between the ages of 12 and 17 years who sustained a mTBI and had between 4 and 16 weeks of persistent post concussive symptoms. DESIGN: Secondary outcome analysis of a partially masked RCT of sub-symptom exacerbation aerobic training compared with a full-body stretching program highlighting cognitive and quality of life outcomes MAIN MEASURES: The secondary outcomes assessed included neurocognitive changes in fluid and crystalized age-adjusted cognition using the National Institutes of Health (NIH) toolbox and self and parent-reported total quality of life using the Pediatric Quality of Life Inventory. RESULTS: Twenty-two percent of eligible participants enrolled in the trial. General linear models did not reveal statistically significant differences between groups. Within group analyses using paired t-tests demonstrated improvement in age-adjusted fluid cognition (t(13)=3.39, p=0.005, Cohen’s d=0.61) and crystalized cognition (t(13)=2.63, p=0.02, Cohen’s d=0.70) within the aerobic training group but no significant improvement within the stretching group. Paired t-tests demonstrated significant improvement in both self-reported and parent-reported total quality of life measures in the aerobic training group (self-report t(13)=3.51, p=0.004, Cohen’s d=0.94; parent-report t(13)=6.5, p<0.0001, Cohen’s d=1.80) and the stretching group (self-report t(14)=4.20, p=0.0009, Cohen’s d=1.08; parent-report t(14)=4.06, p=0.0012, Cohen’s d=1.045). CONCLUSION: Quality of life improved significantly in both the aerobic exercise and stretching groups; however, this study suggests that only sub-symptom exacerbation aerobic training was potentially beneficial for neurocognitive recovery, particularly the fluid cognition subset in the NIH Toolbox. Limited sample size and variation in outcomes measures limited ability to detect between group differences. Future research should focus on developing larger studies to determine optimal timing post injury and intensity of active rehabilitation to facilitate neurocognitive recovery and improve quality of life after mTBI. Trial Registration: NCT02035579